ICoSI 2014 : proceedings of the 2nd International Conference on Sustainable Innovation - Taufik, T.; Prabasari, Indira; Rineksane, Innaka Ageng; Yaya, Rizal; Widowati, Retno; Putra Rosyidi, Sri Atmaja; Riyadi, Slamet; Harsanto, Puji (Springer, 2017)
The 2nd International Conference on Sustainable Innovation emphasizes on natural resources technology and management to support the sustainability of mankind. The main theme of ICoSI 2014 "Technology and innovation challenges in natural resources and built environment management for humanity and sustainability " reflects the needs of immediate action from scientists with different fields and different geographical background to face the global issue on world's change.
Keywords: Sustainable engineering -- Congresses.; elektronické knihy; electronic books